Comparative effectiveness of missed dose protocols of opioid agonist treatment in British Columbia, Canada: protocol for a population-based target trial emulation - Paul Gustafson; Robert W Platt; Bohdan Nosyk; Jeong Eun Min; Md Belal Hossain; Mohammad Ehsanul Karim; Shaun Seaman; Paxton Bach; Megan Kurz; Maria Eugenia Socías; Momenul Haque Mondol; Michelle Zanette (BMJ Open)
Introduction Methadone and buprenorphine/naloxone are effective medications for people with opioid use disorder; however, interruptions in daily dosing are common and diminish the benefits of these medications. While clinical guidelines in most North American jurisdictions, including British Columbia (BC), recommend dose adjustment after treatment interruptions to varying levels of specificity, the evidence to support these recommendations is limited. We aim to estimate the comparative effectiveness of alternative dose adjustment strategies on subsequent overdose-related acute care visits and discontinuation of opioid agonist treatment in BC, Canada.Methods and analysis Using a linkage of nine health administrative databases, we propose a population-level retrospective cohort study of adults aged 18 years or older in BC who initiated methadone or buprenorphine/naloxone between 1 January 2010 and 31 December 2022. We will specify parallel hypothetical trials, known as target trials, for methadone interruptions of 1–3 days, 4 days and 5–14 days, and buprenorphine/naloxone interruptions of 1–5 days and 6–14 days. Following the index interruption, the primary outcomes are the time to overdose-related acute care visits and treatment discontinuation (interruptions lasting >14 days), with time to all-cause acute care visits as a secondary outcome. The intention-to-treat effect will be estimated using both propensity score and instrumental variable approaches. A range of sensitivity analyses will assess the robustness of our results, including cohort and timeline restriction, alternative definitions of exposure and outcome and alternative estimation strategies.Ethics and dissemination The protocol, cohort creation and analysis plan have been classified and approved as a quality improvement initiative by Providence Health Care Research Institute and the Simon Fraser University Office of Research Ethics. All data are deidentified, securely stored and accessed in accordance with provincial privacy regulations. Results will be disseminated to local advocacy groups and decision-makers, national and international clinical guideline developers, presented at international conferences and published in peer-reviewed journals electronically and in print.